2011
DOI: 10.1002/ppul.21390
|View full text |Cite
|
Sign up to set email alerts
|

Can we use portable nitric oxide analyzer in young children?

Abstract: ObjectiveManagement of asthma could be improved by measuring exhaled nitric oxide (FENO). Portable hand‐held FENO analyzer (NIOX MINO) is practical and small and could be used also in the primary care office. It has demonstrated good repeatability and correlation with stationary device (NIOX) in adults and school aged children, but so far there have been no reports on young children. The aim of this study was to compare conventional chemiluminescence device (NIOX) with a hand‐held electrochemical device (NIOX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 14 publications
(2 reference statements)
3
28
0
Order By: Relevance
“…That study revealed poor accuracy at low eNO levels and lower success rates (73%) for the portable device as compared with the stationary device (93%; ref. 26). Their proportion of successfully performed eNOsb measurements among children with a mean age comparable to the majority of our study population, the BILD cohort study participants, was generally higher than ours (67.5% for eNOsb).…”
Section: N = 55mentioning
confidence: 56%
“…That study revealed poor accuracy at low eNO levels and lower success rates (73%) for the portable device as compared with the stationary device (93%; ref. 26). Their proportion of successfully performed eNOsb measurements among children with a mean age comparable to the majority of our study population, the BILD cohort study participants, was generally higher than ours (67.5% for eNOsb).…”
Section: N = 55mentioning
confidence: 56%
“…l One study 47 reported statistically significantly higher mean FeNO values with NIOX MINO whereas two studies 48,49 reported statistically significantly lower values. One of these studies 49 had low mean values (< 10 ppb).…”
Section: Niox Mino Compared With the Niox Chemiluminescent Device In mentioning
confidence: 92%
“…One of these studies 49 had low mean values (< 10 ppb). l All studies reported good correlation between the devices.…”
Section: Niox Mino Compared With the Niox Chemiluminescent Device In mentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies have also shown the feasibility of the 6-s mode in FeNO fractional exhaled nitric oxide children (aged 4-18 years) using the NIOX MINO Ò device [19][20][21][22][23]. This was a one-visit study simply designed in order to evaluate clinical validation of the NIOX VERO Ò device using the 6-s and 10-s modes in young children.…”
Section: Discussionmentioning
confidence: 99%